PKM Pelatihan Microsoft Office 2016 yang Efektif dan Efisien pada HIMPAUDI di Kecamatan Batam Kota - Amrizal Amrizal; Tukino Tukino; Rika Harman (PUAN INDONESIA, 2021)
The development of soft skills at the Association of Early Childhood Educators and Education Personnel in Batam City District can be fulfilled through a Multimedia learning model based on Information and Communication Technology (ICT). The training for developing multimedia learning media based on Information and Communication Technology aims to provide skills in making interesting multimedia learning media in a relatively easy way. The method applied in this activity is the Method of Presentation, Demonstration and Practice. Presentation method is used for software introduction using Microsoft Powerpoint 2016. Demonstration method regarding program operation and Practice Method, namely making learning media directly by participants according to their respective subjects by utilizing these programs. The results of this study are: First, the training provides several materials related to efforts to improve the quality of learning by providing knowledge about the use of the Powerpoint Program to create interactive games as an attractive and interactive ICT-based multimedia learning media, Second, the material presented is acceptable, digestible, and well understood by the participants, Third, the activity went smoothly, on time and as expected.